Resignifying teaching about contagious diseases with an experimental approach in a science fair - Theisen, Geovane Rafael; Zanovello, Regiane; Mattana, Stéfani Dutra; Moresco, Terimar Ruoso; Garlet, Tânea Maria Bisognin (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This paper presents considerations about practical activity realized in a Science Fair organized by participants of the Programa Institucional de Bolsa de Iniciação à Docência PIBID/CAPES, in the subproject of Biological Science of the Universidade Federal de Santa Maria-Palmeira das Missões. The approach was to experimentally demonstrate an disease of contagious for 6th grade students [7th grade] of the a school from primary school in Palmeira das Missões-RS. The presentation of the results of the experiment at the Fair was held by the students where the involvement and integration of the students in the activity was crucial to the successful outcome of the work. The differentiated approach to teaching given disease of contagious served to combine theory with practice and reframe conceptions of environments that non-formal education such as the shows also provide a space for socializing and meaningful dissemination of topics related to the field of Sciences.